2005
DOI: 10.1007/s10549-005-3702-4
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Marital Status on the Stage at Diagnosis, Treatment, and Survival of Older Women with Breast Cancer

Abstract: Research indicates an association between marital status and health but this link has not been thoroughly explored. Our goal was to examine the association of marital status on the diagnosis, treatment, and survival of older women with breast cancer and the potential role socioeconomic status, education level, and comorbidities may play in explaining these associations. Retrospective cohort study using linked Medicare and National Cancer Institute Surveillance, Epidemiology, and End Results cancer registry. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

27
192
3
5

Year Published

2008
2008
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 242 publications
(227 citation statements)
references
References 27 publications
27
192
3
5
Order By: Relevance
“…The lower probability of unmarried women with breast cancer receiving a definitive therapy is not new and has been interpreted as an effect of reduced family support and weaker social networks [19].…”
Section: Discussionmentioning
confidence: 99%
“…The lower probability of unmarried women with breast cancer receiving a definitive therapy is not new and has been interpreted as an effect of reduced family support and weaker social networks [19].…”
Section: Discussionmentioning
confidence: 99%
“…Marriage may have a protective effect on prognosis of cancer patients. Studies indicated that unmarried patients were at higher risk of presentation with metastatic cancer, undertreatment, and shorter survival in various cancer types 3, 4, 5, 6, 7, 8, 9, 10, 11, 12. Mixed 13, 14, 15, 16 or no significant 17, 18, 19 associations between marital status and cancer survival were reported as well.…”
Section: Introductionmentioning
confidence: 99%
“…Although marital status have been commonly identified by various studies (Goodwin et al, 1987;Osborne et al, 2005;Kravdal and Syse, 2011) as a positive factor in earlier cancer diagnosis and better survival, local studies (Parsa and Kandiah, 2010;Rosmawati, 2010) to date have not established any significant link between marriage and uptake of breast cancer screening. Attention should be given as the role of social support in improving screening behaviour needs to be further clarified.…”
Section: Introductionmentioning
confidence: 99%